A efetividade do direito ambiental internacional na proteção da biodiversidade marinha nas áreas além da jurisdição nacional - Nunes, Wolmer Rogério da Cunha (My University, 2017)
The current model of society is based on increasing accumulation of capital, through the relation of consumption, through the exploitation of natural resources, with the corresponding production of negative externalities in the environment. This process evidences the existing social inequality, in which some people have broad access to consumer goods, and the negative externalities are shared among everyone. Thus, there are those who are deprived of minimum conditions for subsistence, bearing the consequences of the system. In this context, the marine exploration has highly relevance in reference of to economic and environmental focus. Pollution from the consumer society, exploitative risky activities and the predatory exploitation of marine resources are elements that affect everyone, with transboundary effects. These externalities are most heavily reliant on the less favored populations, who need the maritime resources for subsistence. Considering the slow regenerative biocapacity of marine biodiversity, the effects of pollution are transgenerational. Given this, the impasse between economic interests versus environmental protection is established. As a way of disciplining matters relating to the seas, the 1982 United Nations Convention on the Law of the Sea was established, delimiting areas under state jurisdiction, among other provisions. Residually was designated Area, comprising the seabed offshore, contained in Part XI of the Convention, and the corresponding water column remains without specific rule. In 2004, the UN established the creation of a working group aiming at the elaboration of a legal instrument for the conservation and sustainable use of marine resources in the high seas, commonly known by the abbreviation ABNJ, derived from the expression areas beyond national jurisdiction. The proposal concerns the establishment of a legally binding instrument. Based on the analysis of the discussions in the research and negotiation groups established by the UN, it was not possible to envisage the predisposition of the main powers to give in to points where they affect economic interests, such as the restriction on exploitation, technology transfer and pecuniary compensation of the exploited resources. Thus, the research problem is the questioning of the effectiveness of international environmental law regarding the protection of marine biodiversity in ABNJ. To unveil the proposed question, the indirect documentation technique was used and as methods the discourse analysis was used in relation to the discussions established in the working groups created by the UN, as well as the hypothetical-deductive method for general analysis of the research. As a result, it was found that the establishment of a soft law would be more likely to succeed in reaching the scope of marine protection. Because it is less restrictive, it would make it possible to attract more States Parties and, therefore, to bind them, even in program norms. In essence, treaty assumption is a form of risk recognition. Based on discourse theory and in view of the multicultural reality, the centrifugal pressure on the politics of each state becomes a crucial element for the effective fulfillment of the treaties.
O atual modelo de sociedade está assentado em acumulação crescente de capital, através da relação de consumo e mediante a exploração de recursos naturais, com a correspondente produção de externalidades negativas no meio ambiente. Esse processo evidencia a desigualdade social existente, em que alguns têm amplo acesso aos bens de consumo, sendo que as externalidades negativas são compartilhadas entre todos. Assim, existem os que se veem privados de condições mínimas para a subsistência, arcando com as consequências do sistema. Nesse contexto, a exploração marinha apresenta grande relevância no que tange aos enfoques econômico e ambiental. A poluição, decorrente da sociedade de consumo, as atividades exploratórias de risco e a exploração predatória dos recursos marinhos são elementos que atingem a todos, com efeitos transfronteiriços. Essas externalidades recaem, com maior vigor, sobre as populações menos favorecidas, necessitadas dos recursos dos mares para a subsistência. Considerando a lenta biocapacidade regenerativa da biodiversidade marinha, os efeitos da poluição apresentam um caráter transgeracional. Diante disso se estabelece o impasse entre interesses econômicos versus proteção ambiental. Como forma de disciplinar as questões relativas aos mares, foi estabelecida a Convenção das Nações Unidas sobre o Direito do Mar, em 1982, delimitando as áreas sob a jurisdição estatal, entre outras disposições. Residualmente, foi designada a Área, compreendendo o leito marinho de alto mar, constante na Parte XI da referida Convenção, sendo que a correspondente coluna de água permanece sem disciplina específica. Em 2004, a ONU estabeleceu a criação de um grupo de trabalho, objetivando a elaboração de um instrumento jurídico destinado à conservação e uso sustentável dos recursos marinhos em alto mar, meio comumente designado pela sigla ABNJ, derivada da expressão areas beyond national jurisdiction. A proposta é relativa ao estabelecimento de um instrumento juridicamente vinculante. Com base na análise dos debates, ocorridos nos grupos de pesquisa e de negociação estabelecidos pela ONU, não foi possível vislumbrar a predisposição das principais potências em ceder nos pontos que afetam os interesses econômicos, tais como a restrição quanto à exploração, transferência de tecnologia e compensação pecuniária pela exploração dos recursos. Assim, o problema de pesquisa é o questionamento da efetividade do direito ambiental internacional quanto à proteção da biodiversidade marinha em ABNJ. Para desvelar a questão proposta, foi utilizada a técnica de documentação indireta e como métodos foram empregados à análise do discurso, no que se refere às discussões estabelecidas nos grupos de trabalho criados pela ONU, bem como foi empregado o método hipotético-dedutivo, para análise geral da pesquisa. Como resultado, foi verificado que o estabelecimento de uma soft law teria maiores possibilidades de êxito em atingir o escopo da proteção marinha. Por ser menos restritiva, possibilitaria uma maior atração de Estados-parte e, com isso, vinculando-os, ainda que em normas programáticas. Em essência, a assunção ao tratado é uma forma de reconhecimento do risco. Tendo como base a teoria do discurso e tendo em vista a realidade multicultural, a pressão centrífuga sobre a política de cada Estado torna-se um elemento importante para o cumprimento efetivo dos tratados.
Keywords: Direito ambiental internacional; Biodiversidade marinha; Direito ambiental - Brasil; Environmental law, international; Environmental law - Brazil; Marine Biodiversity